Vγ9Vδ2 T Cells Activation Through Phosphoantigens Can Be Impaired by a RHOB Rerouting in Lung Cancer - Laplagne, Chloé; Meddour, Sarah; Figarol, Sarah; Michelas, Marie; Calvayrac, Olivier; Favre, Gilles; Laurent, Camille; Fournié, Jean-Jacques; Cabantous, Stéphanie; Poupot, Mary (Frontiers in Immunology, 2020)
Vγ9Vδ2 T cells are known to be efficient anti-tumor effectors activated through phosphoantigens (PAg) that are naturally expressed by tumor cells or induced by amino bisphosphonates treatment. This PAg-activation which is TCR and butyrophilin BTN3A dependent can be modulated by NKG2D ligands, immune checkpoint ligands, adhesion molecules and costimulatory molecules. This could explain the immune-resistance observed in certain clinical trials based on Vγ9Vδ2 T cells therapies. In NSCLC, encouraging responses were obtained with zoledronate administrations for 50% of patients. According to the in vivo results, we showed that the in vitro Vγ9Vδ2 T cell reactivity depends on the NSCLC cell line considered. If the PAg-pretreated KRAS mutated A549 is highly recognized and killed by Vγ9Vδ2 T cells, the EGFR mutated PC9 remains resistant to these killers despite a pre-treatment either with zoledronate or with exogenous BrHPP. The immune resistance of PC9 was shown not to be due to immune checkpoint ligands able to counterbalance NKG2D ligands or adhesion molecules such as ICAM-1 highly expressed by PC9. RHOB has been shown to be involved in the Vγ9Vδ2 TCR signaling against these NSCLC cell lines, in this study we therefore focused on its intracellular behavior. In comparison to a uniform distribution of RHOB in endosomes and at the plasma membrane in A549, the presence of large endosomal clusters of RHOB was visualized by a split-GFP system, suggesting that RHOB rerouting in the PC9 tumor cell could impair the reactivity of the immune response.